Water financing: scaling up finance to the Water, Energy, Food and Environment (WEFE) Nexus - Ravindranath, Darshini; Steele, P. (International Water Management Institute, 2026)
Financing for climate, nature, and development has featured prominently in recent global forums, including Climate COP29, Nature COP16, Desertification COP16, the World Bank/IMF Annual Meetings, and the International Development Association (IDA) replenishment. Yet, despite water being central to climate resilience and sustainable development, water financing remains marginal in global financial discussions. COP29 in Baku underscored the need to scale up adaptation finance through the New Collective Quantified Goal (NCQG), but sectoral priorities—particularly water—received limited attention. Since then, the global climate finance landscape has shifted rapidly, with several governments rolling back climate commitments and reducing public finance, heightening the urgency for private and blended finance solutions.